Implications of the monetary union convergence for the rate of economic growth in Poland - Witold Małecki (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
1) The negotiated terms of Poland's accession to the EU oblige us to accede to the EMU too. However, they do not predetermine the date of our EMU entry. In this paper, four most probable, in the author' opinion, scenarios of our accession to the EMU were presented. Scenario A assumes accession at the earliest possible date, i.e. in 2009-2010. Scenario B1 anticipates a somewhat later EMU membership, i.e. in 2012-2014 because of the inability to fulfil the Maastricht criteria before the end of the current decade. Under scenario B2, like under scenario B1, a more remote accession is assumed, this time however as a result of a deliberate decision of the Polish authorities on postponement of our EMU membership. Finally, scenario C defers our EMU accession into a not precisely defined future in consideration of a permanent inability of the Polish economy to meet the nominal convergence criteria. 2) The main objective of this paper was the attempt at identifying the impact of the above different EMU convergence scenarios on the long-term pace of economic growth in Poland. The main conclusions were formulated basing on two fundamental propositions. The first proposition says that the EMU membership will be advantageous to the long-term economic growth in Poland. Sharpening of the competition resulting from further intensification of the trade and capital flows will create conditions favourable to innovativeness and entrepreneurship. At the same time, the access to the resources of productive factors, especially to capital, will improve. However, the scale of advantages to be achieved and the probability of avoiding serious threats associated with the EMU membership will depend in the first place on the degree of real convergence of the Polish economy with the euro-zone, as well as on the direction of the future evolution of the whole EMU. With a favourable course of events, these long-term advantages to the economic growth can be in the order of 0.5 percentage points a year. The second proposition says that the period preceding the EMU entry (pre-accession period) will generate conditions not very advantageous to the economic growth. Along with the growth-oriented stimuli resulting from the improving economic climate and growing foreign capital inflow, there will also be some marked depressive effects. The latter will stem from the relatively restrictive fiscal and monetary policy imposed by the need of meeting the Maastricht criteria, as well as from the real (and, intermittently, also nominal) appreciation of the zloty. It is to be stressed that both the above propositions were formulated mainly basing on theoretical considerations, since the available empirical material remains very meagre and not always congruent with the Polish economic situation. 3) Our analysis has led to the conclusion that positively best conditions of the economic growth are assured by scenarios A and B2, with a slight preference for the former. However, implementation of these scenarios requires great resoluteness in carrying out the "second wave" of structural reforms as well as discipline in the macroeconomic policy (this, in particular, regards scenario A). In Poland's present political and social situation, this will undoubtedly be difficult. Therefore, unfortunately, it is the B1 scenario that is to be recognized as the most probable from among the scenarios under review, and even scenario C, being a scenario of economic disaster, can not be excluded. 4) On the assumption, however, of a favourable course of events, choice will remain between the scenarios A and B2: to accede to the EMU at the earliest possible date, or deliberately defer the accession by a few years. One of crucial decisions in this respect will have to be made already in 2.5-3.5 years, namely at the time when decision will be necessary whether to enter (or not) the ERM-2. Till that time, the optimum strategy should consist in positively declaring the intention of the possibly earliest EMU entry (and, above all, acting in accordance with such declarations), but without committing oneself by naming any firm dates. Whereas final decisions on the accession to the ERM-2, and later to the EMU, should be made in taking into consideration in the first line the following factors: * the already attained progress not only in the nominal but also in the real convergence, as well assessment of further progress in this respect; * assessment of the utility of maintaining the autonomous monetary and exchange rate policy; * evolution of the EMU itself; * strategy adopted by the remaining new EU members with respect to the question of their EMU accession.
Keywords: 330; Eurozone; Wirtschaftliche Konvergenz; Wirtschaftswachstum; EU-Mitgliedschaft; Polen; EU-Mitgliedschaft